The combination of the economic forecasts using expert information - A. A. Surkov (Статистика и экономика)
Purpose of the study. The aim of this work is to consider the possibility of using expert information when combining forecasts as an additional factor in improving the accuracy of economic forecasting. Using the methodology of combining forecasts is increasingly found in the domestic practice of economic forecasting. Most researchers agree that combining forecasts improves forecasting accuracy by using all available information about the process under study, which is included in individual forecasting methods.  Today, there are many methods for constructing weighting factors when combining forecasts, but all of them are primarily based on the use of only statistical information about the process under study. But economic forecasting cannot be linear in its dynamics, many external factors constantly affect the forecasted process, and some internal ones may not be affected by the methods used. In this case, it is necessary to attract expert information or external information about the forecast obtained in order to increase its accuracy and adjust the further development of the economic process. This is especially true today, during the period of digitalization of the economy and the increasing influence of social and political factors on the dynamics of economic phenomena.  Materials and methods. For this purpose, methods of constructing integral indicators based on expert information or directly using such information at the stage of constructing a joint forecast can be directly used to make adjustments to the resulting combined forecast. Some of these approaches are already used in foreign practice of economic forecasting, while in domestic practice they are still little known. One of such approaches may be the use of the pairwise preference method or the application of Fishburn formulas for ranking particular forecasting methods by accuracy. The approaches considered in this work can be used as tools for constructing weight coefficients or as a correction of the obtained forecasting results.  Results. As a result of this article, attempts have been made to propose possible methods for combining forecasts using expert information, a summary table has been compiled with an assessment of one or another method of combining forecasts, and conclusions are drawn on the appropriateness of their application in practice. Such a table will make it possible to better understand the direction of attracting expert information to combine forecasts and choose the most suitable approach for further use in practice.  Conclusion. Combining forecasts has long established itself as an effective method for increasing forecast accuracy. This technique cannot degrade the result, in most cases increasing accuracy. The use of expert information in combining forecasts is the next step in improving this technique and requires a separate further practical study of possible tools for attracting expert information to the pool.